1776 and Hamilton: Comparing “Founding” Histories in Musical Theatre - Anne Melissa Potter (European Journal of American Studies)
This article analyzes how Hamilton and 1776 address a similar historical moment to engage history about the “founding” of the United States, and how their different engagements with that history reflect the specific cultural moments in which they occur. This article asks how these musicals use the affordances of the musical to comment on controversial aspects of the “founding” that carry contemporary resonances, both in 1969 and 2015: slavery and the future of the country. The two musicals examine these key problems in American history through differences in “who” interacts with and tells these stories in the musicals. Their responses to these issues are also shaped by the political administrations and contexts in place when they were written. 1776 is more critical of the current political system than Hamilton, but both musicals disrupt traditional historical narratives through music.